Prevalence and Characteristics of Neonatal Comfort Care Patients: A Single-Center, 5-Year, Retrospective, Observational Study - Garten, Lars; Ohlig, Sjoukje; Metze, Boris; Bührer, Christoph (Frontiers in Pediatrics, 2018)
Objective: To investigate the prevalence and characteristics of neonates with life-limiting or life-threatening conditions who receive care focused exclusively on comfort. Methods:Retrospective chart review of all newborn infants admitted to a level III perinatal center within a 5 year period. Results:1,777 of 9,878 infants (18.0%) had life-limiting or life-threatening conditions. 149 (1.5% of all neonates) were categorized as comfort care patients with death being anticipated within hours to weeks. 34.2% of comfort care patients suffered from conditions specific to the neonatal period, 28.9% were preterm infants at the limit of viability, and 22.8% were patients with congenital complex chronic conditions. In 80.5% of all comfort care patients treatment goals were re-directed toward a comfort-care-only regimen only once that life-prolonging therapies were demonstrated to be unhelpful. 136/149 comfort care patients (91.3%) died in hospital, while 13 (8.7%) were discharged home or into a hospice. Median age at death for comfort care patients was 3 days after birth (interquartile range 1–15.5 days), and delivery room death immediately after birth occurred in 37 patients (27.2%). Conclusions: The vast majority of neonatal comfort care patients died in the hospital during the first week of life. However, almost one in 10 comfort care patients were discharged to home or hospice, suggesting that planning transition out of the NICU should be routinely discussed for all infants receiving comfort care.